Mudawwanah Al-Usrah dan Pemihakan Terhadap Hak-Hak Perempuan di Maroko - Budi Juliandi; Fauzun Jamal; Saifuddin Herlambang (Proceedings of Annual Conference for Muslim Scholars, 2017)
The main purpose of this paper is to provide a review of Muslim Family Law 004 (Mudawwanah al-Usrah ) in Marocco. Based on literature review, this paper aims to highlight, explain and discuss the family code reform in Morocco. The study indicates that the family code reforms in Morocco do support the rights of women in the family. The reform produces polarization in society, either the supporting group or the rejecting one.